Postpartum endometritis. Incidence and Risk Factors - Pacheco, José (2015)
OBJECTIVE: To determine the incidence and risk factors for puerperal endometritis. DESIGN- Prospective, longitudinal, comparative, and observational study. LOCATION: Department of Obstetrics, Edgardo Rebagliati Martins National Hospital, PSSI. SUBJECTS: 3350 pregnant women who delivered at our Hospital. RESULTS: Puerperal endometritis occurred in 2,6% mainly in primiparae and great multiparae. Rupture of membranes over 6 hours appears as the most important risk factor, followed by cesarean section, prolonged labor, labor induction, number of vaginal examinations and infection of the urinary tract. Cultures grew mainly E. coli. CONCLUSION: Early detection of risk factors would preclude the installation of puerperal endometritis.